2002
DOI: 10.1038/sj.ejcn.1601471
|View full text |Cite
|
Sign up to set email alerts
|

The relation between single/double or repeated tea catechin ingestions and plasma antioxidant activity in humans

Abstract: Objective: The purpose of this study was to investigate the effects of single=double or repeated intake of a normal amount of tea catechin on plasma catechin concentrations and antioxidant activity in young women. Design: First, after an overnight fast, five healthy subjects were given water or single=double dose(s) of tea polyphenol extract (164 mg tea catechins containing 61% epigallocatechin gallate in 190 ml water). Blood samples were taken before and 30, 60 and 180 min after the ingestion. Second, 16 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(57 citation statements)
references
References 28 publications
(32 reference statements)
5
49
1
2
Order By: Relevance
“…anti-carcinogenetic (Kuroda & Hara, 1999;Lin et ul., 1999;Suganuma et ul., 1999, 200_3;Ahmad et a!., 2000;Cao & Cao, 1999;Lambert & Yan_~, 2003), anti-metastatic (Sazuka et a/., 1997; Maeda-Yamamoto et a/., 1999; Isemura et a!., 199_3; Sazuka et a/., 1995), anti-oxidative (Bors & Saran, 1987;Hashimoto et a!., 2003;Okuda et al, 1983;Kimura et a!., 2002), anti-hypertensive (Yokozawa et a!., 1994), anti-hypercholesterolemic (Murase et al, 2002;Chlsaka et a/., 1988; Matsumoto et a!., 1998), anti-dental caries (Sakanaka et a/., 1992;Hattori et a!., 1990), antl-bacterial (Fukai et al, 1991), and intestinal fiora amelioration activity (Okubo et a/., 1992).…”
unclassified
“…anti-carcinogenetic (Kuroda & Hara, 1999;Lin et ul., 1999;Suganuma et ul., 1999, 200_3;Ahmad et a!., 2000;Cao & Cao, 1999;Lambert & Yan_~, 2003), anti-metastatic (Sazuka et a/., 1997; Maeda-Yamamoto et a/., 1999; Isemura et a!., 199_3; Sazuka et a/., 1995), anti-oxidative (Bors & Saran, 1987;Hashimoto et a!., 2003;Okuda et al, 1983;Kimura et a!., 2002), anti-hypertensive (Yokozawa et a!., 1994), anti-hypercholesterolemic (Murase et al, 2002;Chlsaka et a/., 1988; Matsumoto et a!., 1998), anti-dental caries (Sakanaka et a/., 1992;Hattori et a!., 1990), antl-bacterial (Fukai et al, 1991), and intestinal fiora amelioration activity (Okubo et a/., 1992).…”
unclassified
“…They have recently been discovered to have various physiologically modulating effects such as anti-carcinogenic, [1][2][3][4][5][6][7] anti-metastatic, [8][9][10][11] anti-oxidative, [12][13][14][15] antihypertensive, 16) anti-hypercholesterolemic, [17][18][19] antibacterial, 20) anti-dental caries, [21][22][23] and intestinal flora amelioration activities. 24) Caffeine (1, Fig.…”
mentioning
confidence: 99%
“…It is possible that EGCG in nanomolar concentrations causes hydrogen peroxide production in physiological concentrations, which mediates cell signalling pathways, proliferation, and differentiation (30). A study in humans by Kimura et al (31) revealed that ingestion of a single (164 mg) and a double (328 mg) catechin dose in green tea did not change its antioxidant activity because they were conjugated or methylated after absorption by the digestive system. However, antioxidant activity in cells decreased signifi cantly seven days after tea catechin consumption stopped (31).…”
Section: Lipid Peroxidationmentioning
confidence: 99%
“…A study in humans by Kimura et al (31) revealed that ingestion of a single (164 mg) and a double (328 mg) catechin dose in green tea did not change its antioxidant activity because they were conjugated or methylated after absorption by the digestive system. However, antioxidant activity in cells decreased signifi cantly seven days after tea catechin consumption stopped (31).…”
Section: Lipid Peroxidationmentioning
confidence: 99%